Morphological phylogeny and revision of Sycophila and Ficomila (Hymenoptera: Chalcidoidea, Eurytomidae) associated with Afrotropical fig trees (Moraceae, Ficus) - Lotfalizadeh, Hossein; Delvare, Gérard; Cruaud, Astrid; Rasplus, Jean-Yves (Zootaxa, 2024)
Eurytomidae (Chalcidoidea) species associated with fig trees (Ficus) are still poorly documented. A phylogenetic analysis of 63 morphological characters was conducted to revise Afrotropical species of Sycophila Walker and Ficomila Bouček associated with fig trees. Based on our results, which also included Palaearctic species of Sycophila, three subgenera of Sycophila are proposed: Sycophila s. str., Tineomyza Rondani stat. rev. and a new subgenus, Ficorytoma subgen. n. Lotfalizadeh & Rasplus. Ficomila is maintained as a valid genus. Thirty-six species are also newly described by Lotfalizadeh & Rasplus, namely Ficomila artocarpoides sp. n., F. carolae sp. n., F. bouceki sp. n., F. comptoni sp. n., F. flava sp. n., F. gabonensis sp. n., F. gibba sp. n., F. guinensis sp. n., F. sinai sp. n., F. tanzanica sp. n., F. vannoorti sp. n., Sycophila (Tineomyza) beninensis sp. n., S. (T.) busseicola sp. n., S. (T.) glumosae sp. n., S. (T.) luteacola sp. n., S. (T.) maldesi sp. n., S. (T.) minuta sp. n., S. (T.) platygastra sp. n., S. (T.) risbeci sp. n., S. (T.) wiebesi sp. n., S. (T.) zebrogastra sp. n., S. (Ficorytoma) delvarei sp. n., S. (F.) persicae sp. n., S. (Sycophila) annae sp. n., S. (S.) bidentata sp. n., S. (S.) longiflagellata sp. n., S. (S.) chirindensis sp. n., S. (S.) ficophila sp. n., S. (S.) fusca sp. n., S. (S.) lasallei sp. n., S. (S.) macrospermae sp. n., S. (S.) meridionalis sp. n., S. (S.) nigra sp. n., S. (S.) nigriterga sp. n., S. (S.) suricola sp. n., S. (S.) zebra sp. n.. Seven described species of Sycophila are reclassified in the subgenus Tineomyza: Sycophila (Tineomyza) flaviclava Bouček, 1981; S. (T.) modesta Bouček, 1981; S. (T.) naso Bouček, 1981; S. (T.) punctum Bouček, 1981; S. (T.) ruandensis Risbec, 1957; S. (T.) sessilis Bouček, 1981 and S. (T.) setulosa Zerova, 2009. After this revision, Ficomila and Sycophila include 46 species associated with Afrotropical Ficus. Detailed morphological descriptions and illustrations as well as identification keys are provided for the subgenera, species-groups and species of Ficomila and Sycophila associated with Afrotropical fig trees; their host fig association and relative lack of host-specificity are also discussed.